A 3D discrete macro-element for modelling the out-of-plane behaviour of infilled frame structures. (15th November 2018) - Pantò, B.; Caliò, I.; Lourenço, P.B.
Highlights: A discrete macro-model is developed for simulating the out-plane behaviour of IFS. A new 3D nonlinear interface allows the modelling of infill-frame interaction. The model can be employed for seismic assessments of infilled frame structures. The model is validated against refined FEM models and experimental data. Abstract: A high percentage of new and existing framed buildings (either in concrete or steel) are built with unreinforced masonry infilled walls leading to the structural typology known as Infilled Frame Structures (IFS). In these structures, the masonry infills are built after the construction of the main structural frame and are considered as non-structural elements. For this reason, the contribution of unreinforced masonry infills is generally neglected, in the structural analysis of IFS, leading to inaccuracies in the prediction of their seismic nonlinear response. In this paper a three-dimensional discrete element method, able to simulate the complex interactions, in-plane and out-of-plane, in IFS is presented. In the proposed approach, the infill wall is modelled by means of an original spatial discrete element previously introduced for the analysis of UnReinforced Masonry (URM) Structures. Since the attention is focused on the behaviour of the masonry infills, the frame elements have been assumed as linear elastic beams interacting with the macro-elements through plane nonlinear interfaces. In the paper, after a theoretical description of the proposed approach, several experimental–numerical comparisons are provided for investigating the out-plane behaviour of infilled frames. The achieved results demonstrate the accuracy and the significant potential of using the proposed approach for the non-linear analysis of IFS under different loading conditions.